STUDIES ON THE HSHERY OF THE PENAEID PRAWN METAPENAWS AFFINIS (MILNE EDWARDS) ALONG THE MANGALORE COAST - Ramamurthy, S; Kurup, N Surendranatha; Annigeri, G G (Indian Journal of Fisheries, 2011)
With the progressive introduction of mechanised fishing during the last decade and a half, the prawn fishery at Mangalore on the southwest coast registered a substantial increase. Prawns, almost exclusively composed of various species c^ penaeids, form about 35% c^ the trawl catch. Though the’ average annual landing of M. affims is about 110 tonnes constituting only one-nineth of the p^awn catch, this species is of immense importance since it grows to a large size and is of high export value.